Synthesis and Application of New 2-Amino Ethyl Ether of Tamarind Kernel Powder as Ion-Exchanger - Gupta, Vikal; Singh, A.V.; Sindal, R.S.; K. Gupta, Dheerendra (Asian Journal of Chemistry, 2016)
The effects of wastewater from Ankur Mineral Pvt. Ltd and Kothari Metal Industries were studied by sampling and analyzing for some physico-chemical properties between Jan '03 to June '03. The effluent from the industries is discharged to the local river and agriculture areas. Samples were collected before and after discharge point it reveals that the farms and fields were polluted and the level of Cu2+, Zn2+, Pb2+, Cd2+, Mg2+, Ca2+, Fe2+, CN–, SO42– were fairly high. Tamarind kernel powder (TKP) powder obtained from seeds of tamarind plant as a hydrophilic polysaccharide matrix has been used for preparation of a new chelating resin. Ethanolamine derivative of TKP acts as a flocculent-cum-metal ion exchanger and can be used as scavenger for toxic and hazardous metal ions from the effluents of mineral and metallurgical industries. The ethanolamine group was anchored on TKP bake bone in dioxane medium.